Progress on holographic techniques to measure real-time phase and amplitude gratings in photosensitive materials - Cordeiro, CMB; Freschi, A. A.; Cescato, L. (Iop Publishing Ltd, 2003)
In this paper we present and demonstrate a technique that allows simultaneous and independent measurement of small changes in the refractive index and the absorption coefficient produced in photosensitive materials during holographic exposure. The technique is based on the synchronous detection of two-wave mixing signals in both directions of the transmitted interfering beams. By processing both signals it is possible to separate the diffraction contributions of the refractive index from the absorption coefficient and simultaneously stabilize the incident fringe pattern. The demonstration of this technique is undertaken by following the temporal evolution of the phase and amplitude modulations in photoresist films. To check the ability of the technique to perform numeric evaluations, for a positive photoresist the changes in the optical constants were measured and compared with those obtained using independent methods.
Keywords: photosensitive materials; diffraction gratings; holography; optical constants